2013
DOI: 10.1371/journal.pone.0077805
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus-Associated Central Nervous System Diseases after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Herpesvirus infections of the central nervous system (CNS) are associated with encephalitis/myelitis and lymphoproliferative diseases in immunocompromised individuals. As of now, data of herpesvirus-associated CNS diseases in transplant recipients is limited. Hence, in this prospective study, we investigated the incidence of herpesvirus-associated CNS diseases and explored the diagnosis of these diseases in 281 allogeneic hematopoietic stem cell transplantation (allo-HSCT) recipients. Herpesvirus-DNA and cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 28 publications
(28 reference statements)
3
29
0
1
Order By: Relevance
“…Although the presence of HHV‐6 DNA in CSF was detected in only two of four patients, a definite 1.9% (2/105) and a probable 3.8% (4/105) of cases developed HHV‐6 encephalitis in out HSCT population. These incidences were similar to or slightly higher than observed in previous studies [Schmidt‐Hieber et al, ; Ogata et al, ; Wu et al, ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the presence of HHV‐6 DNA in CSF was detected in only two of four patients, a definite 1.9% (2/105) and a probable 3.8% (4/105) of cases developed HHV‐6 encephalitis in out HSCT population. These incidences were similar to or slightly higher than observed in previous studies [Schmidt‐Hieber et al, ; Ogata et al, ; Wu et al, ].…”
Section: Discussionsupporting
confidence: 91%
“…Several previous studies have shown the significance of HHV‐6 reactivation and subsequent HHV‐6 encephalitis in post‐HSCT patients [Schmidt‐Hieber et al, ; Zerr et al, ; Ogata et al, ; Wu et al, ]. In the present prospective study, we coupled a multiplex PCR capable of simultaneously detecting 13 kinds of viruses with a follow‐up quantitative PCR for HHV‐6, and demonstrated the importance of HHV‐6 infection in post‐HSCT subjects who experienced CNS dysfunction.…”
Section: Discussionsupporting
confidence: 59%
“…10,50 However, more recent, albeit smaller, studies show the incidence of EBV-associated PTLD to be higher at 3% to 4%. 6,32,33 Increased incidence of cancers after allogenic transplantation, including those involving the CNS, has also been observed in a large study of 19,229 subjects in which the investigators noted the risk to be higher 5 or more years after transplantation. This increased risk was thought to be likely related to conditioning with radiation, altered immune function, and prior treatment of the primary disease.…”
Section: Neoplastic Disease After Transplantationmentioning
confidence: 81%
“…Causative viruses included herpes simplex virus 1, cytomegalovirus (CMV), varicella-zoster virus, and Epstein-Barr virus (EBV). 6,32 In another study, the incidence of EBV-associated CNS disease, including encephalitis or myelitis, has been reported to be 3.4%, with the median time of disease onset being 49 days (22-184) post-transplant. 33 Although MRI of the brain may be normal in these subjects, focal or diffuse signal FLAIR hyperintensities or space-occupying lesions may also be seen.…”
Section: Viral Infectionmentioning
confidence: 99%
“…Notably, HHV‐6, which is a causative virus in the preponderance of retrospective studies by M. Schmidt‐Hieber et al., was not prevalent in the VE virus spectrum in this study. Likewise, in a prospective study from China about the incidence of herpes virus‐associated CNS diseases in allo‐HSCT recipients, HHV‐6 was not among the causative virus spectrum for VE . Although the basis for the viral spectrum differences remains unclear, the causative spectrum discrepancies might be partly due to regional disparities.…”
Section: Discussionmentioning
confidence: 99%